Choice of the optimal acoustic design of a school classroom and experimental verification. (March 2019) - Russo, Domenico; Ruggiero, Alessandro
Abstract: The acoustic environment in a typical school classroom is often an obstacle for students to listening and learning as well as maintaining attention, sticking to task, speech recognition and reading achievement. In this paper three commonly used scenarios of acoustic correction design of a classroom at an Italian state school were investigated, in order to choose the most favourable acoustical configuration. Subsequently, with reference to the most favourable one, the results of acoustical measurement verification after the realization of the intervention were discussed. First of all a measurement campaign of the main acoustic descriptors (Reverberation Time, Index of Clarity of the Word and Speech Transmission Index) for this kind of location (UNI 11367) using an Integrated Impulse Response (ISO 3382) was carried out, in order to set the parameters of the simulated classroom model. Then the most favourable solution through a low-budget intervention without the need to carry out structural changes is chosen by comparing three different reference scenarios. After built a detailed classroom 3D model and then simulating the considered configurations by using a previsional software (CadnaR), the improved acoustic effects were achieved using sound-absorbant panels placed appropriately on the walls and the ceiling, in order to obtain optimal acoustics in school setting at reasonable cost. The choice of the sound absorbant panels was made accounting for four common materials and investigating on their behaviour in terms of both absorption/frequency and antibacterial-fireproofing properties connected with the use in a scholar environment. The detailed analysis of the measured acoustic parameters after the completion of the intervention, according to the choosed configuration, allows the authors to conclude that the realized intervention shows a very good agreement with the simulated one and represents the optimal configuration in terms of acoustic performances and of a cost-benefit return. Moreover the results of this investigation can be used as a general design guide for acoustic engineers involved in these kind of design.